Antifungal and growth promoting activities of new rhizospheric bacterial isolates from sago palm in Agusan Marsh - Siarot, Lowela Libunao (2007)
Three rhizospheric bacteria obtained from sago palm in Agusan marsh were tested for their ability to improve tomato growth and suppress pathogen growth. Bacterial strains Rh1-MS-CO, Rh2-MS-CO, Rh3-MS-CO exhibited antifungal activities against Penicillium and Curvularia but none with Pestalotiopsis as evidenced by the appearance of zones of inhibition. Diamante and Improved Pope varieties of tomato subjected to rhizospheric isolates and varying concentrations of gibberellic acid achieved a high percent germination, which implies high viability of seeds. The growth response of tomato seedlings in terms of the parameters evaluated such as percent germination and rate of germination, shoot length, root length increase and root and shoot dry weights did not differ significantly between the two varieties except that the Diamante variety had significantly longer radicles than Improved Pope. Regardless of of variety, the responses of seeds to all treatments were similar. Rhizospheric bacteria did not increase the rate of germination, percent germination and radicle lengths of tomato seedlings for both varieties. In terms of shoot length, only seedlings treated with Rh3-MS-CO developed longer shoots than the untreated seedlings, which may be due to bacterial gibberellin production. In root growth experiment, among the bacteria-treated seedlings, only Rh3-MS-CO developed shorter root length increases than the untreated seedlings. Root and shoot dry weights of seedlings treated with bacterial strains Rh2-MS-CO and Rh3-MS-CO did not differ from the untreated seedlings while Rh1-MS-CO had lower root and shoot dry weights than the untreated seedlings. The growth promotion via shoot length increase in Diamante and Improved Pope varieties and the antifungal activities against Penicillium and Curvularia show the potential of the three rhizospheric bacteria as PGPR. This also suggests that three rhizospheric isolates are worth screening for plant growth promotion.